A scenario for the development and use of teaching oriented ontologies. (11th August 2009) - Belesiotis, V.S.; Alexandris, N.
In this paper we propose a methodology for the construction and use of Teaching-Oriented Ontologies and present how such ontologies can support the lesson planning phase and the teaching process. We present their pilot use with focus on the Greek secondary-education system. We then present our arguments supporting their use, suggest a methodology for the development of such ontologies and explain how teaching-oriented ontologies can aid the teaching process. Finally, we demonstrate an example of the use of our methodology and discuss the findings of an empirical evaluation of its use by teachers during the lesson planning phase.